2020
DOI: 10.3389/fped.2020.00571
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intraobserver Variation in the Assessment of Preoperative Colostograms in Male Anorectal Malformations: An ARM-Net Consortium Survey

Abstract: Aim: Male patients with anorectal malformations (ARM) are classified according to presence and level of the recto-urinary fistula. This is traditionally established by a preoperative high-pressure distal colostogram that may be variably interpreted by different surgeons. The aim of this study was to evaluate the inter-and intraobserver variation in the assessment by pediatric surgeons of preoperative colostograms with respect to the level of the recto-urinary fistula. Materials and Methods: Sixteen pediatric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A correct classification of the ARM is necessary to appropriately address the follow-up and management of possible complications. A uniform classification of ARM is also mandatory to make series comparable between centers ( 2 , 6 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A correct classification of the ARM is necessary to appropriately address the follow-up and management of possible complications. A uniform classification of ARM is also mandatory to make series comparable between centers ( 2 , 6 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Midrio et al ( 6 ), on behalf of the ARM-Net Consortium, reported a poor agreement among experienced pediatric colorectal surgeons on preoperative colostograms of males with ARM. In fact, the agreement between the image-based rating of surgeons and the intraoperative findings ranged from 0.06 to 0.45, and the interobserver variation was very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation